Building life cycle applied to refurbishment of a traditional building from Oporto, Portugal. (May 2018) - Rodrigues, Fernanda; Matos, Raquel; Alves, Ana; Ribeirinho, Paulo; Rodrigues, Hugo
Abstract: Buildings management along with its life cycle is currently an issue that requires a great optimisation considering the high cost associated with the buildings use and due to the operation and maintenance costs. The number of existing buildings needing refurbishment actions justify the need of an intervention model that optimise its service life after the refurbishment process. So, a refurbishment, maintenance and costs planning should be established and guided by value for money principles. The aim of this paper is to analyse the application of Buildings Life Cycle Management (BLCM) to a case study under a refurbishment process, to study the specific solutions and to assess the correspondent service life using the factor method according the ISO 15686 family. With this study, was possible to assess solutions and refurbishment conditions in terms of durability, when compared between the different proposals. In order to improve the case study Building Life Cycle maintenance, in addition, was applied Building Information Modelling (BIM), as BLCM is connected with BIM in order to highlight the importance of their inter-relationship. This study concludes about the most advantageous type of maintenance, how BIM can contributes to BLCM and how can improve maintenance plans. Thus, this study contributes to highlight the importance of preventive maintenance, to promote its implementation and consequently, to use maintenance plans reducing life cycle cost and increasing materials service life.